NCHD handover in the acute mental health setting: a quality improvement initiative implementing an electronic handover tool - Karen O’Connor; Stelios Naxakis; Megan Wafer; Syeda Gardezi; Aamina Sadia; Rimsha Mujahid (BMJ Open Quality)
Background Cork University Hospital, Ireland’s largest teaching hospital, faced challenges in maintaining consistent handover processes in its Acute Mental Health Unit (AMHU). Prior to 2019, handovers relied on informal methods, risking information loss and compromising patient care. This quality improvement (QI) initiative aimed to standardise handover practices using an electronic tool integrated with the ISBAR communication protocol.Objectives The project aimed to ensure accurate clinical information recording, improve patient care and safety, centralise handover material, enhance clinical transparency and accountability, and measure handover quality using the electronic tool.Methods Using a Plan-Do-Study-Act (PDSA) model, the initiative began with a critical incident in July 2020, prompting the creation and piloting of an electronic ‘handover tool’ aligned with ISBAR. Subsequent PDSA cycles included mandatory policy implementation and educational interventions to reinforce tool usage and adherence to communication standards.Results The electronic handover tool improved handover practices, with increased compliance to recommended criteria and enhanced tool utilisation. Notable improvements followed targeted educational interventions, leading to more comprehensive and standardised handover entries. These improvements enhanced communication and information transfer among NCHDs, contributing to better continuity of care and patient safety.Conclusions The QI initiative successfully standardised handover processes and improved communication among NCHDs in the AMHU. While improvements were observed, ongoing efforts are needed to address challenges and sustain effectiveness. Continuous training, feedback mechanisms and further refinement of the handover tool are essential for long-term success. Future directions include exploring additional technological solutions and reinforcing a culture of effective communication.